Superbase‐Promoted Selective Cascade Cyclization Reaction of 1, 5‐Diketones with Acetylenes to Methylene‐6, 8‐dioxabicyclo[3.2.1]octanes. Issue 12 (11th March 2013) - Schmidt, Elena Yu.; Bidusenko, Ivan A.; Protsuk, Nadezhda I.; Ushakov, Igor A.; Trofimov, Boris A.
Abstract: 1, 5‐Diketones are readily cyclized in the presence of various alkali‐metal superbases with acetylenes at 70 °C in a one‐pot cascade reaction to give methylene‐6, 8‐dioxabicyclo[3.2.1]octanes in up to 92 % yield. In the case of symmetrical 1, 5‐diketones, only one diastereomer is formed, whereas unsymmetrical diketones afford two diastereomers in a ratio corresponding to that of the starting ketones. This result indicates the key cascade cyclization sequence is stereoselective. Abstract : From 1, 5‐diketones and acetylenes to polysubstituted methylene‐6, 8‐dioxabicyclooctanes, versatile building blocks and pheromones scaffold: a one‐pot transition‐metal‐free approach.